Optimalisasi Website untuk Monitoring Jaringan OPD di Dinas Kominfo Kota Medan dengan Metode Triangulasi - Andi Zulherry; Farid Akbar Siregar; Zuli Agustina Gultom; Elza Ahmad Raihan (Bulletin of Computer Science Research, 2023)
This study aims to optimize the use of a website as a tool for monitoring the network of Local Government Agencies (OPD) at the Department of Communication and Informatics (Kominfo) of Medan City using the triangulation method. The triangulation method involves the use of observation, interviews, and documentation to gain a more comprehensive understanding of the effectiveness of the website as a network monitoring tool. During the observation phase, the researcher conducted direct observations of user interactions with the monitoring website and understood the dynamics of its usage. Interviews with users and network administrators were conducted to gain direct insights into the strengths and challenges in using the website. Technical data and network performance reports were also obtained from existing documentation. The results of this study illustrate how the triangulation method can provide a deeper understanding of the effectiveness of the monitoring website. Observation revealed user interaction patterns with the website interface, interviews provided user perspectives on usability and desired improvements, and documentation provided technical context. The conclusion of this study is that the use of the triangulation method yields a more comprehensive understanding of issues and opportunities in optimizing the website for OPD network monitoring. It is expected that the results of this study will provide valuable guidance for the development and enhancement of more effective website features for monitoring OPD networks. This contributes to better and more responsive information technology infrastructure management in the local government setting.